Case report: a case of hypoparathyroidism–sensorineural deafness–renal dysplasia syndrome - Yang, Jinyan; Mei, Yanjie; Tang, Feifei; Guo, Xinhong; Kong, Yanhua; Deng, Ying (Frontiers in Genetics, 2025)
This article reports a case of a young woman who was admitted to the hospital with “sudden convulsions for 3 h.” She was diagnosed with hypoparathyroidism and found to have sensorineural deafness and left renal agenesis. A diagnosis of hypoparathyroidism–sensorineural deafness–renal dysplasia (HDR) syndrome was established, and the patient was treated with calcium and active vitamin D. After 2 years of follow-up, her blood calcium levels continued to fluctuate significantly. Subsequently, a heterozygous variant in the GATA3 gene (NM_001002295.2:c.404dup) was detected. According to the literature, patients with HDR syndrome require low doses of active vitamin D supplementation. Excessively high blood calcium levels should be avoided, and treatment should be individualized.